The Year 2020 in Review: Noteworthy Literature for Thoracic Transplant Anesthesiologists. (June 2021) - Abrams, Benjamin A.; Wilkey, Barbara
The year 2020 was a monumental year in medicine, and this review focuses on selected articles for cardiothoracic anesthesiologists and perioperative physicians involved in the care of heart and lung transplant patients. In the field of lung transplantation, significant strides were made in our knowledge of risk stratification during the preoperative assessment of potential recipients, perioperative transfusion medicine, and the administration of coagulation factor concentrates. In addition, variations in perioperative management and outcomes between institutions were studied across an assortment of metrics regarding lung transplantation, including case volumes and anesthetic practices. Transitioning to topics in the field of heart transplantation, consideration was given to recipients with adult congenital heart disease, and separately, approaches to expanding the donor pool through donation after circulatory death. With regard to preoperative support, outcomes for the total artificial heart as well as the MitraClip as bridges to transplantation were published.